Kewenangan Pengawasan Dan Pembinaan Notaris Sebagai Pejabat Lelang Kelas II Berdasar Undang-Undang Jabatan Notaris - Linta Ulinnuha Bahraine (Faculty of Law Universitas Islam Indonesia, 2024)
Notaries can serve as Class II Auction Officials and have the authority to make Auction Minutes. Two provisions regulate this, namely the Auction Regulations and the Notary Law, which give rise to various interpretations. The problems raised are two, namely, first, whether Notaries are immediately authorized to make Auction Minutes, second, how is the authority to supervise and guide Notaries as Class II Auction Officials based on UUJN. This research is normative legal research with a statutory approach that aims to analyze the authority and supervision of notaries. The results of the study show that first, Notaries cannot immediately make Auction Minutes unless the Notary is appointed as an Auction Official. Second, the authority to supervise and guide Notaries is carried out by the Notary Supervisory Board, while the Auction Official is carried out by the Auction Supervisor (Superintendent). The authority of the Notary Supervisory Board is limited to Auction Minutes as stated in Article 15 paragraph (2) of UUJN.Keywords: Notary Authority, Auction, Supervision and Development. AbstrakNotaris dapat menjabat sebagai Pejabat Lelang kelas II dan memiliki kewenangan membuat Risalah Lelang. Terdapat dua ketentuan yang mengatur yakni Peraturan Lelang dan Undang-Undang Jabatan Notaris sehingga menimbulkan beragam interpretasi. Permasalahan yang diangkat ada dua yaitu, pertama apakah Notaris serta merta berwenang dalam membuat Risalah Lelang, kedua bagaimana kewenangan pengawasan dan pembinaan Notaris sebagai Pejabat Lelang kelas II berdasar UUJN. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan yang bertujuan untuk menganalisis kewenangan dan pengawasan notaris. Hasil penelitian menunjukkan pertama Notaris tidak serta merta dapat membuat Risalah Lelang kecuali Notaris diangkat sebagai Pejabat Lelang. Kedua kewenangan pengawasan dan pembinaan Notaris dilakukan oleh Majelis Pengawas Notaris sedangkan Pejabat Lelang dilakukan oleh Pengawas Lelang (Superintenden). Kewenangan Majelis Pengawas Notaris terbatas pada Risalah Lelang sebagaimana disebutkan dalam Pasal 15 ayat (2) UUJN.Kata kunci: Kewenangan Notaris, Lelang, Pengawasan dan Pembinaan.